2018
DOI: 10.1016/j.atmosres.2018.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Performances of GPM satellite precipitation over the two major Mediterranean islands

Abstract: Abstract. Obtaining accurate high-resolution precipitation fields is still a challenging task. Nowadays, continuous technological evolution of satellite-rainfall estimate systems, which are able to produce low-cost data with a global coverage, are giving significant improvements in precipitation monitoring. The Global Precipitation Measurement (GPM) is the most recent satellite mission and a promising source of rainfall estimates at high spatial and temporal resolutions. The aim of this study is to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 53 publications
10
20
0
Order By: Relevance
“…Except for RB, the two post-time products (IMERG_F and 3B42) perform significantly better than the rest real-time or near real-time products both annually and seasonally, with a noticeably higher value of CC (e.g., 0.97 and 0.95 annually) as well as considerably lower values of RMSE (e.g., 53.82 and 54.13 mm annually), and MAD (e.g., 35.79 and 37.07 mm annually) ( Table 2). The findings of the overall better performance of the two post-time SPPs products compared to the real-time or near real-time products at the monthly time scale are not surprising, since both are generated after the adjustment of real-time products based on monthly measurements of ground rain gauges [42], although which may not include the 13 rain gauges covered in our study.…”
Section: Evaluation At the Monthly Scalementioning
confidence: 95%
See 1 more Smart Citation
“…Except for RB, the two post-time products (IMERG_F and 3B42) perform significantly better than the rest real-time or near real-time products both annually and seasonally, with a noticeably higher value of CC (e.g., 0.97 and 0.95 annually) as well as considerably lower values of RMSE (e.g., 53.82 and 54.13 mm annually), and MAD (e.g., 35.79 and 37.07 mm annually) ( Table 2). The findings of the overall better performance of the two post-time SPPs products compared to the real-time or near real-time products at the monthly time scale are not surprising, since both are generated after the adjustment of real-time products based on monthly measurements of ground rain gauges [42], although which may not include the 13 rain gauges covered in our study.…”
Section: Evaluation At the Monthly Scalementioning
confidence: 95%
“…Similar to our study, they have mostly found that the performance of SPPs in estimating hourly rainfall was less satisfactory. For example, Caracciolo et al [53] calculated the CCs to be respectively 0.32 and 0.26 when using the IMERG_F V4 for estimating hourly rainfall in Sardinia and Sicily of Italy. Li et al [54] evaluated the performance of IMERG_F in estimating hourly rainfall in the Ganjiang River Basin of China, and calculated its CC, RMSE, and RB to be 0.33, 1.72 mm/h, and 0.12%, respectively.…”
Section: Continuous Evaluation Metricsmentioning
confidence: 99%
“…The description of these symbols refers to Gao et al [36]. The mathematical expressions of these indexes are the following [11,37]:…”
Section: Diagnostic Statisticsmentioning
confidence: 99%
“…Integrated multi-satellite retrievals have three half-hourly products that provide rainfall from March 2014 to the present. Unlike its predecessor, the Tropical Rainfall Measuring Mission (TRMM), GPM can better detect light rainfall and snow as a result of the new dual-frequency precipitation radar, and a conical-scanning higher frequency multichannel GPM microwave imager [18]. In 2015, the Climate Hazard Group released the 0.05 • × 0.05 • resolution Climate Hazard Group's InfraRed Precipitation with Stations (CHIRPS) dataset, which provides quasi-global daily rainfall data [19].…”
Section: Introductionmentioning
confidence: 99%